Tafsir MK Atas Pasal 33 UUD 1945: Studi Atas Putusan MK Mengenai Judicial Review Terhadap UU No. 7/2004, UU No. 22/2001, dan UU No. 20/2002 - Magnar, Kuntana; Junaenah, Inna; Taufik, Giri Ahmad (Mahkamah Konstitusi Republik Indonesia, 2010)
The rulings of the constitutional court to review the Act No. 7 of 2004 on Management of Water Resources, Act No. 22 of 2001 on Crude Oil and Natural Gas, Act No. 20 of 2002 on Electricity caused controversy. These decisions gives a different interpretation of Article 33 of the Constitution of 1945, which likely have implications for Indonesia’s economic development policy. Branches of production which is important for the livelihoods of people and natural resources, is placed in the area of public law rather than private. The consequences are arranged by state control rights as a collective representation of Indonesian society. Thus, the form that allows management of a joint is through cooperatives and the state delegation of the management of public goods to the non-state (cooperative), can only be done with the instrument of one-sided legal action.